Modulation of total cholesterol and triglyceride in plasmodium Berghei infected mice by aqueous crude extract of Andrographis Paniculata - Sairung Sriwiphat (2018)
© 2015, College of Public Health Sciences. All rights reserved. During malaria infection in erythrocytes, critical markers including total cholesterol and triglyceride are markedly increased. Hence, finding new medicinal plants to have homeostatic effect on these markers during malaria infection are urgently needed. Andrographis paniculata is a medicinal plant and widely cultivated in Southeast Asia. This plant exhibits antioxidant property and is used to treat liver disorder and control lipid profile. In this study, we assessed changes in plasma total cholesterol and triglyceride levels accompanying Plasmodium berghei ANKA infection in mice treated orally with aqueous crude extract of A. paniculata at 100, 300, and 600 mg/kg. Significant increases of total cholesterol and triglyceride levels in plasma were observed in infected untreated mice compared to normal control. However, treatment with 300 and 600 mg/kg of the extract produced significant reduction in plasma total cholesterol and triglyceride compared to untreated mice. Moreover, prolonged survival time was found in infected mice treated with this extract. It can be concluded that the extract has anti-hyperlipemic property during malaria infection that can be explored for the management of malaria.